INTEGRATING SIMPLE PAST TENSE IN PRIMARY SCHOOL ENGLISH CURRICULUM: A STUDY OF TEACHING STRATEGIES - Hasby, Nazar; Misrita, Misrita; Putri, Librina Tria (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2024)
This research explored effective teaching strategies for teaching elementary school students the simple past tense. Given that children at primary school age experienced rapid cognitive development, appropriate teaching methods were essential for building a strong language foundation. This article reviewed teaching methods in the simple past tense, including Communicative Language Teaching (CLT), Game-Based Learning (GBL), and technology integration. CLT prioritized the use of language in accurate and relevant contexts, which helped students understand the use of the simple past tense in everyday conversations. Game-based learning (GBL) increased student engagement and motivation through interactive games, such as card and role-playing games, which facilitated the understanding of tense changes in a fun way. In addition, technologies such as language learning apps and interactive videos provided opportunities for students to practice independently and receive immediate feedback. The research also highlighted the importance of student motivation in successful teaching, where a supportive environment and fun activities increased student engagement and understanding of the material. The results of this research suggested that the combination of CLT, GBL, and technology methods, as well as the cultivation of student motivation, could create a compelling and engaging learning environment.